Tobacco use among school going children - Ankita Verma; Mridula Goswami; Jatinder Kaur Dhillon (Wolters Kluwer Medknow Publications, 2019)
Background: Despite increasing awareness of harmful effects of tobacco, its use in various forms continues to be significant health risk factors among children. Aim: To assess the prevalence, pattern, and age of initiation of tobacco consumption, various factors influencing the habit of tobacco consumption, correlation between the educational status of children and their habit of tobacco consumption, and evaluation of any tobacco-induced oral lesion among 8-14 years of school going children in Central Delhi zone. Methods and Materials: Total sample of 500 students aged 8-14 years from two schools in Central Delhi were studied using a structured, close ended, prevalidated questionnaire after taking prior permission and inform consent from the school authority. In the end, intraoral examination was done and health educational session was conducted to make students aware of health hazards of tobacco products. Results: Prevalence of tobacco consumption among students was 16.4%. Out of total 82 tobacco users, 89% were male, whereas 11% were female. Smokeless tobacco consumption was predominant with Gutka being most preferred. Mean age of initiation of smoking form of tobacco was 9.57 ± 1.13 year, whereas for smokeless form, it was 9.25 ± 1.16 years. Friends (78.04%) were most common influencing factors, followed by family member (12.2%) and media (9.7%). Conclusion: The rate of tobacco use was high, considering very young age group of this study. Consumption of tobacco among children is an emerging health problem in Central Delhi zone. Mandatory health education sessions against tobacco should be held regularly for students, teachers, and parents.